Edukasi Penanganan Nyeri Punggung Bawah pada Ibu Hamil melalui Kompres Hangat Water Bag - Faozi, Lukman Aqil; Ningrum, Ema Wahyu; Triana, Noor Yunida (Yayasan Inspirasi El Burhani, 2025)
Introduction: Back pain is common during pregnancy, especially in the second and third trimesters. Pregnancy-related back pain has become a complex problem, an unpleasant emotional and sensory experience resulting from actual or potential tissue damage. Pain reduction techniques can be pharmacological or non-pharmacological. Applying a water bag or water pillow to the body is known as a